2017
DOI: 10.1002/ece3.3171
|View full text |Cite
|
Sign up to set email alerts
|

The thermal niche of Neotropical nectar‐feeding bats: Its evolution and application to predict responses to global warming

Abstract: The thermal niche of a species is one of the main determinants of its ecology and biogeography. In this study, we determined the thermal niche of 23 species of Neotropical nectar‐feeding bats of the subfamily Glossophaginae (Chiroptera, Phyllostomidae). We calculated their thermal niches using temperature data obtained from collection records, by generating a distribution curve of the maximum and minimum temperatures per locality, and using the inflection points of the temperature distributions to estimate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…Thus, overexploitation promotes population decline, leading to some cases of local extinction (e.g., Agave potatorum, Delgado-Lemus et al, 2014). There are no studies addressing the pollination system in A. maximiliana but, given the general aspects described above, i.e., paniculate inflorescences, probable nocturnal anthesis dehiscence and geographic area overlapping with that of Leptonycterys yerbabuenae, L. nivalis Saussure, 1860 (Arita, 1991) and Choeronycteris mexicana Tschudi, 1844 (Arroyo-Cabrales et al, 1982;Ortega-García et al, 2017), we infer a chiropterophilous syndrome, with these bat species as likely pollinators.…”
Section: Introductionmentioning
confidence: 79%
“…Thus, overexploitation promotes population decline, leading to some cases of local extinction (e.g., Agave potatorum, Delgado-Lemus et al, 2014). There are no studies addressing the pollination system in A. maximiliana but, given the general aspects described above, i.e., paniculate inflorescences, probable nocturnal anthesis dehiscence and geographic area overlapping with that of Leptonycterys yerbabuenae, L. nivalis Saussure, 1860 (Arita, 1991) and Choeronycteris mexicana Tschudi, 1844 (Arroyo-Cabrales et al, 1982;Ortega-García et al, 2017), we infer a chiropterophilous syndrome, with these bat species as likely pollinators.…”
Section: Introductionmentioning
confidence: 79%
“…Our results show the same trend; all species distribution models change in a similar fashion by shifting up in elevation. A study of the thermal niche phylogenetic patterns in nectar feeding bats found that the two most cold-adapted species are L. nivalis and Choeronycteris mexicana 41 . Both occur in mountainous regions of Mesoamerica and are particularly sensitive to warming climates.…”
Section: Discussionmentioning
confidence: 99%
“…Climatic models project a range of temperature increase of around 1.5–2.8°C (IPCC, 2014); thus, nectarivorous bats are more likely to be challenged by warmer, rather than colder temperatures. Ortega‐García et al, (2017) estimated the thermal niche of several nectar‐feeding bats species using information on occurrence data and found that these species share a similar tolerance to high temperatures, but their lower thermal niche (colder temperatures) is highly variable. However, climatic tolerance (thermal niche width) is positively related to geographic range, where widely distributed species have higher ranges of tolerance to thermal ranges (Ortega‐García et al, 2017).…”
Section: Discussionmentioning
confidence: 99%